Uganda Poverty Assessment : Strengthening Resilience to Accelerate Poverty Reduction - World Bank (Washington, DC : World Bank, 2022)
The share of Uganda’s population that lives below the poverty line has fluctuated over the last seven years, greatly influenced by shocks that have tested the resilience of the people. About 30 percent of the country’s population was poor in 2019-20, which is comparable to the poverty rate of 30.7 percent in 2012-13. The pattern of fluctuating poverty rates is largely driven by the experience of rural households. There was a surge in the poverty rate between 2012-13 and 2016-17, linked to the drought in 2016-17, followed by improvement in 2019-20 prior to the pandemic, when favorable weather conditions helped lift rural incomes. The COVID-19 pandemic pushed both urban and rural residents into poverty. Inequality, which reflects the extent to which different population groups benefit from Gross Domestic Product (GDP) growth, and affects the transmission of growth into poverty reduction, remained largely unchanged over this period and may even have worsened in urban areas. The rest of this overview presents key findings of the report. The next section synthesizes key facts about Uganda’s poverty reduction experience up to 2020. These facts set the stage for the section that follows examining reasons behind limited progress in poverty reduction. The final section reviews the key policy points for action. The report’s analysis is based on new analysis of available data sources as well as published analytical reports such as the Systematic Country Diagnostic Update (World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency 2021), the Country Economic Memorandum (World Bank 2022), and the previous Poverty Assessment (World Bank 2016).